PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING PADA KELURAHAN WANASARI - Fitra Hayyunisha Putri; Milda Handayani; Dhian Tyas Untari (Jurnal Ilmiah Akuntansi, 2026)
This study aims to analyze the effect of brand image, product quality, and price on purchasing decisions of Scarlett Whitening products in Wanasari Village. A quantitative approach with a causal associative design was employed. Data were collected through questionnaires distributed to 140 respondents who had used Scarlett Whitening products, selected using purposive sampling technique. The data were analyzed using multiple linear regression with SPSS software. The results show that brand image, product quality, and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. The findings suggest that strengthening brand image, improving product quality, and setting appropriate prices can enhance consumer purchasing decisions. This study provides insights for future research to include other relevant variables.